RELIGIOUS SYMBOLISM IN INDONESIA - Muhammad Edy Susilo; Arif Wibawa (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2014)
There is a very interesting phenomenon in the religious in this country. On the surface, there was tremendous excitement in religious expression. In the past two decades, moslem women wearing the hijab is still something